AVALIAÇÃO MICROBIOLÓGICA MOLECULAR DOS SÍTIOS PERIIMPLANTARES E PERIODONTAIS DE PACIENTES PARCIALMENTE EDÊNTULOS - Piero, Lorrany de Barros Del (2020)
Evidence related to oral microbiota from individuals treated with osseointegrated implants has been well documented in recent years, however still remains inconclusive. Objective: To evaluate the periimplantar and subgingival microbiota of patients rehabi